Determining overpotentials for the oxidation of alcohols by molecular electrocatalysts in non-aqueous solvents. Issue 10 (24th August 2022) - Speelman, Amy L.; Gerken, James B.; Heins, Spencer P.; Wiedner, Eric S.; Stahl, Shannon S.; Appel, Aaron M.
Abstract : Overpotentials are assessed for electrocatalytic oxidation of alcohols using molecular complexes in organic solvents. This work enables meaningful comparison of electrocatalysts across solvents and conditions to establish essential design criteria. Abstract : Molecular electrocatalysts for energy-related transformations offer unique opportunities to elucidate mechanistic principles that contribute to improved rates and energy efficiency. New catalysts for electrochemical alcohol oxidation in non-aqueous conditions have been developed recently, but it is difficult to make meaningful performance comparisons between them because the different conditions used for each catalyst result in unquantified differences in driving force. The present report outlines an approach to determine the equilibrium potential for the oxidation of alcohols in organic solvents or solvent mixtures. These equilibrium potentials are then used to determine the overpotentials for a series of molecular electrocatalysts. Overall, the methodology outlined herein provides a foundation for future advances in this field and enables comparison of electrocatalyst performance under aqueous and non-aqueous reaction conditions.